Olefin metathesis in multiblock copolymer synthesis - Gringolts, Maria L.; Denisova, Yulia I.; Finkelshtein, Eugene Sh.; Kudryavtsev, Yaroslav V. (Beilstein Journal of Organic Chemistry, 2019)
Multiblock copolymers constitute a basis for an emerging class of nanomaterials that combine various functional properties with durability and enhanced mechanical characteristics. Our mini-review addresses synthetic approaches to the design of multiblock copolymers from unsaturated monomers and polymers using olefin metathesis reactions and other ways of chemical modification across double C=C bonds. The main techniques, actively developed during the last decade and discussed here, are the coupling of end-functionalized blocks, sequential ring-opening metathesis polymerization, and cross metathesis between unsaturated polymers, or macromolecular cross metathesis. The last topic attracts special interest due to its relative simplicity and broad opportunities to tailor the structure and hence the properties of the copolymer products. Whenever possible, we analyze the structure–property relations for multiblock copolymers and point to their possible practical applications.
Keywords: ADMET; macromolecular cross metathesis; multiblock copolymers; olefin metathesis; ROMP

(untitled) - Bielawski, C. W.; Grubbs, R. H. (Prog. Polym. Sci., 2007)

Handbook of Metathesis. Vol. 3: Applications in Polymer Synthesis - Grubbs, R. H. (Wiley-VCH Verlag GmbH & Co, 2003)

Handbook of Metathesis. Vol. 3: Polymer Synthesis - Grubbs, R. H.; Khosravi, E. (Wiley-VCH Verlag GmbH & Co, 2015)

(untitled) - Verduzco, R.; Li, X.; Pesek, S. L.; Stein, G. E. (Chem. Soc. Rev., 2015)

(untitled) - Liberman-Martin, A. L.; Chu, C. K.; Grubbs, R. H. (Macromol. Rapid Commun., 2017)

(untitled) - Yu, Y.-G.; Chae, C.-G.; Kim, M.-J.; Seo, H.-B.; Grubbs, R. H.; Lee, J.-S. (Macromolecules, 2018)

(untitled) - Descour, C.; Macko, T.; Schreur-Piet, I.; Pepels, M. P. F.; Duchateau, R. (RSC Adv., 2015)

(untitled) - Bates, C. M.; Bates, F. S. (Macromolecules, 2017)

(untitled) - Bates, F. S.; Hillmyer, M. A.; Lodge, T. P.; Bates, C. M.; Delaney, K. T.; Fredrickson, G. H. (Science, 2012)

Temperature-Responsive Polymers: Chemistry, Properties, and Applications - Constantinou, A. P.; Georgiou, T. K. (Thermoresponsive Multiblock Copolymers: Chemistry, Properties and Applications, 2018)

Sequence-Controlled Polymers - Lutz, J.-F. (Wiley-VCH Verlag GmbH & Co, 2017)

(untitled) - Bates, C. M.; Maher, M. J.; Janes, D. W.; Ellison, C. J.; Willson, C. G. (Macromolecules, 2014)

(untitled) - Topham, P. D.; Parnell, A. J.; Hiorns, R. C. (J. Polym. Sci., Part B: Polym. Phys., 2011)

(untitled) - Abetz, V. (Macromol. Rapid Commun., 2015)

(untitled) - Kim, H.-C.; Park, S.-M.; Hinsberg, W. D. (Chem. Rev., 2010)

(untitled) - Hillmyer, M. (Curr. Opin. Solid State Mater. Sci., 1999)

(untitled) - Riegler, S.; Slugovc, C.; Trimmel, G.; Stelzer, F. (Macromol. Symp., 2004)

(untitled) - Schacher, F. H.; Rupar, P. A.; Manners, I. (Angew. Chem., Int. Ed., 2012)

(untitled) - de Gennes, P. G. (Faraday Discuss. Chem. Soc., 1979)

(untitled) - Fleury, G.; Bates, F. S. (Macromolecules, 2009)

(untitled) - Angerman, H.; ten Brinke, G.; Erukhimovich, I. (Macromolecules, 1996)

(untitled) - Subbotin, A.; Klymko, T.; ten Brinke, G. (Macromolecules, 2007)

(untitled) - Govorun, E. N.; Chertovich, A. V. (J. Chem. Phys., 2017)

(untitled) - Houdayer, J.; Müller, M. (Macromolecules, 2004)

(untitled) - Chertovich, A. V.; Guseva, D. V.; Kudryavtsev, Y. V.; Litmanovich, A. D. (Polym. Sci., Ser. A, 2008)

(untitled) - Gavrilov, A. A.; Kudryavtsev, Y. V.; Khalatur, P. G.; Chertovich, A. V. (Chem. Phys. Lett., 2011)

(untitled) - Govorun, E. N.; Gavrilov, A. A.; Chertovich, A. V. (J. Chem. Phys., 2015)

(untitled) - Ueda, M. (Prog. Polym. Sci., 1999)

(untitled) - Chum, P. S.; Swogger, K. W. (Prog. Polym. Sci., 2008)

(untitled) - Lutz, J.-F. (Acc. Chem. Res., 2013)

(untitled) - Soeriyadi, A. H.; Boyer, C.; Nyström, F.; Zetterlund, P. B.; Whittaker, M. R. (J. Am. Chem. Soc., 2011)

(untitled) - Alsubaie, F.; Anastasaki, A.; Wilson, P.; Haddleton, D. M. (Polym. Chem., 2015)

(untitled) - Engelis, N. G.; Anastasaki, A.; Nurumbetov, G.; Truong, N. P.; Nikolaou, V.; Shegiwal, A.; Whittaker, M. R.; Davis, T. P.; Haddleton, D. M. (Nat. Chem., 2017)

(untitled) - Martin, L.; Gody, G.; Perrier, S. (Polym. Chem., 2015)

(untitled) - Litmanovich, A. D.; Platé, N. A.; Kudryavtsev, Y. V. (Prog. Polym. Sci., 2002)

(untitled) - Maeda, T.; Otsuka, H.; Takahara, A. (Prog. Polym. Sci., 2009)

(untitled) - Ayres, N.; Weck, M. (Polym. Chem., 2012)

(untitled) - Ghassemi, H.; McGrath, J. E.; Zawodzinski, T. A., Jr (Polymer, 2006)

(untitled) - You, Y.-Z.; Zhou, Q.-H.; Manickam, D. S.; Wan, L.; Mao, G.-Z.; Oupický, D. (Macromolecules, 2007)

(untitled) - Zhang, H.; Shen, P. K. (Chem. Rev., 2012)

(untitled) - Zhang, J.; Bates, F. S. (J. Am. Chem. Soc., 2012)

(untitled) - Lee, I.; Bates, F. S. (Macromolecules, 2013)

(untitled) - Liu, G.; Guan, Y.; Wen, T.; Wang, X.; Zhang, X.; Wang, D.; Li, X.; Loos, J.; Chen, H.; Walton, K.; Marchand, G. (Polymer, 2011)

(untitled) - Lee, I.; Panthani, T. R.; Bates, F. S. (Macromolecules, 2013)

(untitled) - Park, C. H.; Lee, C. H.; Guiver, M. D.; Lee, Y. M. (Prog. Polym. Sci., 2011)

(untitled) - Ilyin, S. O.; Malkin, A. Y.; Kulichikhin, V. G.; Denisova, Y. I.; Krentsel, L. B.; Shandryuk, G. A.; Litmanovich, A. D.; Litmanovich, E. A.; Bondarenko, G. N.; Kudryavtsev, Y. V. (Macromolecules, 2014)

(untitled) - Li, S.; Register, R. A.; Weinhold, J. D.; Landes, B. G. (Macromolecules, 2012)

(untitled) - Choi, T.-L.; Grubbs, R. H. (Angew. Chem., 2003)

(untitled) - Trnka, T. M.; Grubbs, R. H. (Acc. Chem. Res., 2001)

(untitled) - Nomura, K.; Schrock, R. R. (Macromolecules, 1996)

(untitled) - Miyamoto, Y.; Fujiki, M.; Nomura, K. (J. Polym. Sci., Part A: Polym. Chem., 2004)

(untitled) - Rahman, M. A.; Lokupitiya, H. N.; Ganewatta, M. S.; Yuan, L.; Stefik, M.; Tang, C. (Macromolecules, 2017)

(untitled) - Alonso-Villanueva, J.; RodrÍGuez, M.; Vilas, J. L.; Laza, J. M.; León, L. M. (J. Macromol. Sci., Part A: Pure Appl. Chem., 2010)

(untitled) - Liaw, D.-J.; Wu, P.-L. (J. Mol. Catal. A: Chem., 2000)

(untitled) - Pitet, L. M.; Zhang, J.; Hillmyer, M. A. (Dalton Trans., 2013)

(untitled) - Banik, S. M.; Monnot, B. L.; Weber, R. L.; Mahanthappa, M. K. (Macromolecules, 2011)

(untitled) - Mahanthappa, M. K.; Lim, L. S.; Hillmyer, M. A.; Bates, F. S. (Macromolecules, 2007)

(untitled) - Bishop, J. P.; Register, R. A. (Macromolecules, 2010)

(untitled) - Miki, K.; Kimura, A.; Oride, K.; Kuramochi, Y.; Matsuoka, H.; Harada, H.; Hiraoka, M.; Ohe, K. (Angew. Chem., Int. Ed., 2011)

(untitled) - Ahmed, E.; Morton, S. W.; Hammond, P. T.; Swager, T. M. (Adv. Mater., 2013)

(untitled) - Ding, L.; Zhang, L.; Yang, D.; Huang, W.; Xie, M.; Zhang, Y. (Polymer, 2010)

(untitled) - Copenhafer, J. E.; Meyer, T. Y. (Polym. Prepr., 2005)

(untitled) - Abdellatif, M. M.; Nomura, K. (ACS Macro Lett., 2012)

(untitled) - Nomura, K.; Haque, T.; Onuma, T.; Hajjaj, F.; Asano, M. S.; Inagaki, A. (Macromolecules, 2013)

(untitled) - Hu, N.; Mai, C.-K.; Fredrickson, G. H.; Bazan, G. C. (Chem. Commun., 2016)

(untitled) - Gutekunst, W. R.; Hawker, C. J. (J. Am. Chem. Soc., 2015)

(untitled) - Xia, Y.; Olsen, B. D.; Kornfield, J. A.; Grubbs, R. H. (J. Am. Chem. Soc., 2009)

(untitled) - Kim, J. G.; Coates, G. W. (Macromolecules, 2012)

(untitled) - Murphy, J. J.; Kawasaki, T.; Fujiki, M.; Nomura, K. (Macromolecules, 2005)

(untitled) - Xie, M.; Wang, W.; Ding, L.; Liu, J.; Yang, D.; Wei, L.; Zhang, Y. (J. Polym. Sci., Part A: Polym. Chem., 2010)

(untitled) - Hilf, S.; Kilbinger, A. F. M. (Macromolecules, 2009)

(untitled) - Hilf, S.; Kilbinger, A. F. M. (Macromolecules, 2009)

(untitled) - Moatsou, D.; Nagarkar, A.; Kilbinger, A. F. M.; O'Reilly, R. K. (J. Polym. Sci., Part A: Polym. Chem., 2016)

(untitled) - Yang, S. K.; Ambade, A. V.; Weck, M. (Chem. – Eur. J., 2009)

(untitled) - Meng, X.; Tang, G.-R.; Jin, G.-X. (Chem. Commun., 2008)

(untitled) - Zou, Y.; Wang, D.; Wurst, K.; Kühnel, C.; Reinhardt, I.; Decker, U.; Gurram, V.; Camadanli, S.; Buchmeiser, M. R. (Chem. – Eur. J., 2011)

Olefin Metathesis and Metathesis Polymerization - Ivin, K. J.; Mol, J. C. (Academic Press, 1997)

(untitled) - Bertrand, A.; Hillmyer, M. A. (J. Am. Chem. Soc., 2013)

(untitled) - Monfette, S.; Fogg, D. E. (Chem. Rev., 2009)

(untitled) - Gutiérrez, S.; Tlenkopatchev, M. A. (Rev. Latinoam. Metal. Mater., 2009)

(untitled) - Michel, X.; Fouquay, S.; Michaud, G.; Simon, F.; Brusson, J.-M.; Carpentier, J.-F.; Guillaume, S. M. (Eur. Polym. J., 2017)

(untitled) - Wagner, N. L.; Timmers, F. J.; Arriola, D. J.; Jueptner, G.; Landes, B. G. (Macromol. Rapid Commun., 2008)

(untitled) - Otsuka, H.; Muta, T.; Sakada, M.; Maeda, T.; Takahara, A. (Chem. Commun., 2009)

(untitled) - Maeda, T.; Kamimura, S.; Ohishi, T.; Takahara, A.; Otsuka, H. (Polymer, 2014)

(untitled) - Ohishi, T.; Suyama, K.; Kamimura, S.; Sakada, M.; Imato, K.; Kawahara, S.; Takahara, A.; Otsuka, H. (Polymer, 2015)

(untitled) - Radlauer, M. R.; Matta, M. E.; Hillmyer, M. A. (Polym. Chem., 2016)

(untitled) - Daniele, S.; Mariconda, A.; Guerra, G.; Longo, P.; Giannini, L. (Polymer, 2017)

(untitled) - Gringolts, M. L.; Denisova, Y. I.; Shandryuk, G. A.; Krentsel, L. B.; Litmanovich, A. D.; Finkelshtein, E. S.; Kudryavtsev, Y. V. (RSC Adv., 2015)

(untitled) - Denisova, Y. I.; Gringolts, M. L.; Krentsel’, L. B.; Shandryuk, G. A.; Litmanovich, A. D.; Finkelshtein, E. S.; Kudryavtsev, Y. V. (Polym. Sci., Ser. B, 2016)

(untitled) - Denisova, Y. I.; Gringolts, M. L.; Peregudov, A. S.; Krentsel, L. B.; Litmanovich, E. A.; Litmanovich, A. D.; Finkelshtein, E. S.; Kudryavtsev, Y. V. (Beilstein J. Org. Chem., 2015)

(untitled) - Denisova, Y. I.; Gringolts, M. L.; Roenko, A. V.; Shandryuk, G. A.; Finkelshtein, E. S.; Kudryavtsev, Y. V. (Mendeleev Commun., 2017)

(untitled) - Shandryuk, G. A.; Denisova, Y. I.; Gringolts, M. L.; Krentsel, L. B.; Litmanovich, A. D.; Finkelshtein, E. S.; Kudryavtsev, Y. V. (Eur. Polym. J., 2017)

(untitled) - Denisova, Y. I.; Gringolts, M. L.; Krentsel’, L. B.; Shandryuk, G. A.; Peregudov, A. S.; Finkelshtein, E. S.; Kudryavtsev, Y. V. (Polym. Sci., Ser. B, 2017)

(untitled) - Naga, N.; Kikuchi, G.; Toyota, A. (Polymer, 2006)

(untitled) - Bornand, M.; Chen, P. (Angew. Chem., Int. Ed., 2005)

(untitled) - Schleyer, P. v. R.; Williams, J. E.; Blanchard, K. R. (J. Am. Chem. Soc., 1970)

(untitled) - Denisova, Y. I.; Roenko, A. V.; Gringolts, M. L.; Krentsel, L. B.; Peregudov, A. S.; Shandryuk, G. A.; Finkelshtein, E. S.; Kudryavtsev, Y. V. (Polym. Sci., Ser. B, 2019)

(untitled) - Digner, M. B.; Mol, J. C. (Eur. J. Inorg. Chem., 2003)

(untitled) - Edwards, M. G.; Jazzar, R. F. R.; Paine, B. M.; Shermer, D. J.; Whittlesey, M. K.; Williams, J. M. J.; Edney, D. D. (Chem. Commun., 2004)

(untitled) - Lee, L.-B. W.; Register, R. A. (Macromolecules, 2005)

(untitled) - Morontsev, A. A.; Denisova, Y. I.; Gringolts, M. L.; Filatova, M. P.; Shandryuk, G. A.; Finkelshtein, E. S.; Kudryavtsev, Y. V. (Polym. Sci., Ser. B, 2018)

(untitled) - Müller, A. J.; Arnal, M. L. (Prog. Polym. Sci., 2005)

(untitled) - Müller, A. J.; Michell, R. M.; Pérez, R. A.; Lorenzo, A. T. (Eur. Polym. J., 2015)